The Role of Bacteria in the Pathogenesis of Ulcerative Colitis - Sasaki, Maiko (Hindawi Publishing Corporation, 2012)
Factors implicated in the pathophysiology of ulcerative colitis (UC) are an abnormal immune response, defect in intestinal epithelial barrier function, and gut microbiota. Currently, it is unclear whether specific bacterial strains are responsible for the induction of intestinal inflammation, but increased bacterial tissue invasion has been described in affected UC patients. Further, a quantitative and qualitative microbial imbalance in UC, defined as dysbiosis, has been characterized by an increase in Rhodococcus spp., Shigella spp., and Escherichia spp., but a decrease in certain Bacteroides spp.. More specifically, Campylobacter spp., Enterobacteriae, and enterohepatic Helicobacter were more prevalent in tissue sample from UC patients subjected to molecular detection methods, but not controls. In addition, serologic testing identified Fusobacterim varium as a potential contributor to the intestinal inflammation in UC. Interestingly, in-situ hybridization studies have shown anti-inflammatory Lactobacillus spp. and Pediococcus spp. were absent in samples from subjects affected by UC. Therefore, dysbiosis is a factor in the pathogenesis of UC.